2008
DOI: 10.1016/j.bbabio.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative phosphorylation and energetic status are reflected by morphology of mitochondrial network in INS-1E and HEP-G2 cells viewed by 4Pi microscopy

Abstract: Mitochondria in numerous cell types, especially in cultured cells, form a reticular network undergoing constant fusion and fission. The three dimensional (3D) morphology of these networks however has not been studied in detail to our knowledge. We have investigated insulinoma INS-1E and hepatocellular carcinoma HEP-G2 cells transfected with mitochondria-addressed GFP. Using 4Pi microscopy, 3D morphology changes responding to decreased oxidative phosphorylation and/or energetic status could be observed in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 85 publications
4
69
0
Order By: Relevance
“…As previously stated, this switch frequently occurs along with fragmentation of the mitochondrial network [22,99]. For example, a correlation between mitochondrial fission and glycolysis is observed in Survivin-overexpressing neuroblastoma cells [100] and 3-BrPA-treated urinary bladder cancer cells [101].…”
Section: Mitochondrial Dynamics and Cell Metabolismmentioning
confidence: 70%
“…As previously stated, this switch frequently occurs along with fragmentation of the mitochondrial network [22,99]. For example, a correlation between mitochondrial fission and glycolysis is observed in Survivin-overexpressing neuroblastoma cells [100] and 3-BrPA-treated urinary bladder cancer cells [101].…”
Section: Mitochondrial Dynamics and Cell Metabolismmentioning
confidence: 70%
“…Recently, 4Pi microscopy, which has higher axial resolution, was employed to examine the mitochondrial morphology of pancreatic b-cells. Image analyses revealed that mitochondria of rat islet b-cells form highly interconnected reticulum similar to those observed in the insulinoma b-cell line (49,134). In contrast, disintegration of tubular mitochondrial network was observed in islet b-cells from diabetic Goto Kakizaki rats (49).…”
Section: Mitochondrial Dynamics In Pancreatic B-cells and Insulin Secmentioning
confidence: 86%
“…In contrast, impaired mitochondrial fusion can result in the loss of ⌬⌿m and a reduction in oxidative phosphorylation (OXPHOS) (Olichon et al, 2003;Chen et al, 2005). It has been suggested that ATP production via OXPHOS results in the production of highly networked mitochondria, whereas glycolysis-dependent ATP production leads to the generation of more spherical mitochondria, although this has yet to be established in neuronal cells (Plecitá -Hlavatá et al, 2008). In the experiments reported here, we did not differentiate between OXPHOS-and glycolysis-related ATP production; however, our results would support the hypotheses that the concentrations of OPs evaluated did not compromise ⌬⌿m or OXPHOS-dependent ATP production or that they drove mitochondrial fusion to maintain OXPHOS-dependent ATP and preserve mitochondrial function.…”
Section: Chlorpyrifos Alters Mitochondrial Dynamics 347mentioning
confidence: 99%